Bubble detection and sector trading in real time. Issue 2 (1st February 2019) - Milunovich, George; Shi, Shuping; Tan, David
Abstract : We conduct a pseudo real-time analysis of the existence and extent of speculative bubbles in 11+ US sectors over the period January 1973–May 2015. Based on computed bubble signals, a trading strategy is constructed which switches funds between the market index and those industry sectors that exhibit bubble dynamics. Our strategy generates the highest after-transaction-cost return and Sharpe ratio, and first-order stochastically dominates a range of alternative strategies we consider, including the buy-and-hold investment in the market index. Subsample analysis and specification checks confirm the robustness of our findings.